2010
DOI: 10.1002/lary.20884
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies comparison of mucosal wave properties using high‐speed digital imaging

Abstract: Objectives The purpose of this study was to compare the vocal fold vibratory characteristics of ex vivo bovine, canine, ovine, and porcine larynges to human male and female vocal fold vibrations to determine the best model organism for laryngeal studies concerning vibratory and kinetic characteristics. Study Design Prospective experimental Methods High speed videos were gathered at 4000 frames per second (fps) in the animal models and human high-speed endoscopy data were gathered at 2000 fps. Videos were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
2
17
0
3
Order By: Relevance
“…Mucosal wave properties of the larynx was compared by Regner et al between ex vivo bovine, canine, ovine, and porcine laryngeal vibration and in vivo human laryngeal vibration using high speed digital imaging. 18 They reported that “no statistically significant differences were found with respect to frequency, amplitude, or phase difference between canines and humans. Porcines were not significantly different from human females but did have an oscillation frequency significantly different from human males.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal wave properties of the larynx was compared by Regner et al between ex vivo bovine, canine, ovine, and porcine laryngeal vibration and in vivo human laryngeal vibration using high speed digital imaging. 18 They reported that “no statistically significant differences were found with respect to frequency, amplitude, or phase difference between canines and humans. Porcines were not significantly different from human females but did have an oscillation frequency significantly different from human males.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine VFs are the focus of this work owing to their structural similarity to human VFs [30][31][32][33][34][35] and the availability of tissue samples of varying age and gender. The LP of 38 pigs, varying in age from fetal to 2 + -year olds, were tested using the TWE.…”
mentioning
confidence: 99%
“…Surprisingly, in a large number of these experiments, larynges of various mammalian species (e.g. dogs, pigs, sheep, cows, rabbits, or rats (Alipour and Jaiswal, 2008;Welham et al, 2009;Regner et al, 2010;Maytag et al, 2013)) were utilized as a proxy for the human vocal organ, probably for ethical reasons. It is sometimes assumed that the vocal fold vibratory characteristics and sound output data from these species are largely comparable with those of their human counterpart (Jiang et al, 2001a;Regner et al, 2010;Alipour et al, 2013).…”
Section: Application Of Excised Larynx Experimentation To Human Voicementioning
confidence: 99%
“…dogs, pigs, sheep, cows, rabbits, or rats (Alipour and Jaiswal, 2008;Welham et al, 2009;Regner et al, 2010;Maytag et al, 2013)) were utilized as a proxy for the human vocal organ, probably for ethical reasons. It is sometimes assumed that the vocal fold vibratory characteristics and sound output data from these species are largely comparable with those of their human counterpart (Jiang et al, 2001a;Regner et al, 2010;Alipour et al, 2013). It should, however, be taken into consideration that the anatomical layout of the vocal folds (particularly that of the lamina propria) differs between these species and humans (Kurita et al, 1983;Garrett et al, 2000), thus potentially leading to different biomechanical properties of the vocal folds and consequently resulting in diverse vibratory characteristics and sound output.…”
Section: Application Of Excised Larynx Experimentation To Human Voicementioning
confidence: 99%